A SYSTEMATIC LITERATURE REVIEW ON SUSTAINABILITY AND USE OF ARTIFICIAL INTELLIGENCE IN TOURISM AND HOSPITALITY: TRENDS AND CHALLENGE - Sengar, Akansha; Kumari, Urvashi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Tourism and hospitality are increasingly recognized as significant drivers of the economy in India. While the concept of sustainability has been extensively discussed in social and scientific research for the past two decades, its application to the hospitality sector is a relatively recent focus. This application raises several challenges but also presents opportunities for competitive advantage. In this research paper, we aim to explore the concept of sustainability in hospitality, conducting a theoretical review of key research areas and suggesting future avenues for investigation. This digital era has introduced new challenges to companies, affecting operations on a global scale and transforming relationships and behaviours. Because nowadays everything revolves around digital media; making it one of the most important modes of communication such as use of AI and smart sensors, IOT( Internet of Things) like Alexa to promote sustainability. This research contributes to the fields of sustainability, tourism, hospitality, and communication. We conclude with future guidelines for research and practice in these areas.